Ethno-religious neighbourhood infrastructures and the life satisfaction of immigrants and their descendants in Germany. (November 2022) - Wiedner, Jonas; Schaeffer, Merlin; Carol, Sarah
Urban research assigns immigrant enclaves an ambiguous role. While such areas are seen as rich in beneficial ethno-religious infrastructures and networks, they also tend to be located in deprived and stigmatised inner-city neighbourhoods. Research on neighbourhood attainment provides evidence for both, a desire to attain mainstream middle-class neighbourhoods, which grows the more immigrants and their descendants establish themselves in society, but also a continuing attraction of residing close to co-ethnics. To tease apart this ambiguity, we study how the life satisfaction of immigrants and their descendants depends on the characteristics of the neighbourhood they live in, and pay special attention to heterogeneity along generation, country of origin orientation and income. We use classic measures of neighbourhood quality vis-à-vis newly collected data on the spatial density of ethno-religious minority associations, places of worship and grocers. We link these data to the geocoded German Socio-Economic Panel to predict life satisfaction among immigrants and their descendants. To strengthen a causal interpretation of our results, we employ specifications that address self-selection into neighbourhoods and unobserved confounding. Contra the assumptions of standard assimilation models, we document that ethno-religious infrastructures contribute to increased life satisfaction primarily among the second generation, and there especially among sending-country oriented individuals. This suggests a continuing importance of origin-culture infrastructures for some groups. Furthermore, we find little evidence that overall neighbourhood quality, or the mere share of co-ethnics in a neighbourhood, increases life satisfaction either among immigrants or their descendants.